The redox transformations and nucleophilic replacements as possible metabolic reactions of the drug “Triazaverin”. The chemical modeling of the metabolic processes - N. R. Medvedeva; I. S. Sapozhnikova; V. L. Rusinov; E. N. Ulomsky (Chimica Techno Acta)
As a model of metabolic transformations of antiviral drug “Triazaverin” and its analogues‑2-alkylthio‑6-nitro‑1,2,4-triazolo[5,1-c][1,2,4]triazine‑7-ones 1a-d examined the oxidation of alkylthio groups to the corresponding sulfoxides 2a-d and sulfones 3a-d, as well as the process of nucleophilic substitution sulfonyloxy group of cysteine and cysteamine with the formation of compounds 5 and 6.